A műértő avagy a konjunktív tudás a modern társadalomban: A művészet fogalmi tere (Szociológiai Szemle, 2024)
First presented at the Mannheim session of the ’100 ans de sociologie’ conference (Paris, June 1993), the paper focuses on the particular type of knowledge required for participation in the modern art world. It argues that Karl Mannheim’s analysis of the connoisseur in his posthumously published Structures of Thinking, provides an illuminating account of the emergence, functions, diffusion, institutionalization and transformations of connoisseurship as one of the forms of a community-bound, conjunctive knowledge.